Return-to-work support for employees with mental health problems: Identifying and responding to key challenges of sick leave. (May 2016) - Cameron, Josh; Sadlo, Gaynor; Hart, Angie; Walker, Carl
Introduction: This research explored return-to-work and sick leave experiences of workers with mental health issues in contact with acute or community mental health services. Method: Using a critical realist methodology with a comparative case study and collaborative design, 21 employed participants recovering from mental health problems participated in semi-structured interviews. Data were analysed using inductive and deductive thematic and constant comparative analysis. Findings: While on sick leave, despite a range of challenges, participants treasured their work identities. They were sustained by positive and troubled by negative memories of work. People missed the routine of work and felt isolated. To varying degrees of success, they searched for alternative activities to fill this gap and promote recovery. Conclusion: The need for sick leave was not disputed, but an important discovery was its iatrogenic ('side-') effects, whereby isolation and reduced activity levels could exacerbate mental health problems. Negative impacts of sick leave need to be mitigated by support to maintain worker identity and orientation and by opportunities and encouragement to sustain routine, activities and social contacts. A new concept of 'occupational capital' emerged, comprising accessible external opportunities and supports for occupational participation, and internal capacities and skills required to access these.